2013
DOI: 10.1074/jbc.m113.479766
|View full text |Cite
|
Sign up to set email alerts
|

A Reducing Milieu Renders Cofilin Insensitive to Phosphatidylinositol 4,5-Bisphosphate (PIP2) Inhibition

Abstract: Background: Cofilin is a key molecule for actin dynamics whose activity can be locally inhibited by PIP2.Results: Changes in the cofilin structure upon reduction render cofilin insensitive to PIP2 inhibition.Conclusion: Local effects of PIP2 on cofilin activity are determined by the redox microenvironment.Significance: We discovered a mechanism of spatio-microenvironmental control of actin dynamics by cofilin reduction at the plasma membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Consistent with this, instantaneous chromophore-assisted laser inactivation revealed that active cofilin normally promotes lamellipodial F-actin turnover [ 24 ]. An additional potential contributing factor is that oxidized cofilin at plasma membranes is likely to be inactivated by membrane lipid association, unlike reduced cofilin that was shown to be insensitive to phosphatidylinositol 4,5-bisphosphate (PIP 2 )-induced inhibition [ 25 ]. Furthermore, cofilin oxidation might reduce competition with myosin II for F-actin binding, thereby enabling development of actin-myosin cortical tension that contributes to cell motility independent of F-actin turnover [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, instantaneous chromophore-assisted laser inactivation revealed that active cofilin normally promotes lamellipodial F-actin turnover [ 24 ]. An additional potential contributing factor is that oxidized cofilin at plasma membranes is likely to be inactivated by membrane lipid association, unlike reduced cofilin that was shown to be insensitive to phosphatidylinositol 4,5-bisphosphate (PIP 2 )-induced inhibition [ 25 ]. Furthermore, cofilin oxidation might reduce competition with myosin II for F-actin binding, thereby enabling development of actin-myosin cortical tension that contributes to cell motility independent of F-actin turnover [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation and thereby inactivation of cofilin is mediated by LimKinase (LimK) and testis‐specific kinases (TES kinases) (reviewed in ). The involvement of PP1 in cofilin regulation could recently be confirmed by knockdown of PP1 in untransformed human T cells . The contribution of the other enzymes to the regulation of cofilin in untransformed T cells remains to be analyzed in detail.…”
Section: Cofilin Activation Induced By T‐cell Costimulationmentioning
confidence: 94%
“…Upon specific stimuli, including a so far unknown cellular reductase, the reduction of cofilin prevents the inhibition by PIP 2 , resulting in increased actin dynamics, e.g. in the immune synapse of untransformed T cells [106]. The Cys39-Cys147 intermolecular disulfide was confirmed in vivo and was shown to be important for the cofilin-actin rod formation in neurons [108].…”
Section: Redox Regulation Of Cofilin Activitymentioning
confidence: 95%
“…Following protein expression cofilin-1 contains at least one disulfide bridge in vivo, possibly involving Cys39 and Cys80, that is susceptible to reduction [106]. The authors furthermore claimed, that the surfaces Cys139 and Cys147 are most likely essential for protein oligomerization, a process that has been described for cofilin-1 before [107][108][109].…”
Section: Redox Regulation Of Cofilin Activitymentioning
confidence: 95%
See 1 more Smart Citation